Social media and e-learning in response to seismic events: Resilient practices - Susan P. C. Tull; Nicki Dabner; Kofi Ayebi-Arthur (Flexible Learning Association of New Zealand, 2017)
The motivation to adopt innovative communication and e-learning practices in education settings can be stimulated by events such as natural disasters.  Education institutions in the Pacific Rim cannot avoid the likelihood of natural disasters that could close one or more buildings on a campus and impact their ability to continue current educational practices. For one university, the impetus to innovate was a series of seismic events. This paper presents findings from studies that identified resilient practices within this 'late adopter' university in New Zealand. The findings indicate that the combined use of social media and e-learning to support teaching, learning, communication and related organisational practices fosters resilience for students, staff and organisations in times of crises. Recommendations are presented that have relevance to all educational organisations which could be impacted by similar events.